KINERJA FERMENTASI SAGU ASAM MENGGUNAKAN STARTER CAIR DAN PADAT DARI ISOLAT BAKTERI ASAM LAKTAT INDIGENOUS - Dedy Suseno, Anja Meryandini, dan Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
In eastern part of Indonesia, sago starch is usually used as staple food. Most of sago starch produced from traditional processing unit which not used clean potable water for its starch extraction, and the starch was kept and stored as wet starch.This causes the spontaneous fermentation of starch to become sour sago starch and contaminated by pathogenic microorganisms; which made the starch not suitable for human consumption and has short product self-life. Fruit water from settling process of starch slurry was used as microbe isolates source. Compared to solid starter, liquid starter showed high adaptation and ability to grow during fermentation, and it caused high acid accumulation in fermentation broth and dried sago starch. Fermentation process could improve the quality of sago starch, but its viscoamylography characteristic tended to reduce on peak viscosity and end viscosity lower. Sour sago had good quality since it could minimize the microbial contamination, especially pathogenic microorganisms.Keywords: lactic acid bacteria, fermentation, nanoporous sago, sour sago starch, solid starter